FENOMENUL TRAFICULUI DE FIINŢE UMANE ÎN REPUBLICA MOLDOVA - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2007)
This article describes a problem that persist in present in different countries: Traffic of human beings. It describes the factors of the traffic of human beings, gives a lot of examples of statistics of traffic of human beings. At the end it gives the resolution: what kind of measures have to be taken in order to exclude traffic of human beings.